Efek Social Media Influencer pada Keputusan Pembelian Produk Kecantikan Somethinc (The Effect of Social Media Influencers on Somethinc Beauty Product Purchase Decisions) - Hanum, Risma Laila; Ruspitasari, Widi Dewi (Akutansi Bisnis & Manajemen ( ABM ), 2024)
Social media is not only an online platform for consumers to communicate and share their lives, but also as a platform for consumers to buy clothes, food, and daily necessities as an online marketing channel. Influencers widely use this to introduce products, which are expected to attract consumers to the products used by influencers. This study aims to determine the relationship between the influence of perceived value on purchase decisions mediated by social media marketing. This study also looks at the relationship between homophily and social media influencers. Respondents in this study were 96 respondents who were users of somethic products distributed via google form, using path analysis with PLS software. The research findings prove that perceived value positively affects social media influencers. Social media mediates the relationship between perceived value and purchase intention. Homophily has a positive relationship with social media influencers.